Hubungan Kerja Petani dan Buruh Tani dalam Meningkatkan Kesejahteraan di Desa Klompangan, Ajung, Jember - Alfan Jamil Efendi; Fiyoga Bayu Saputra; Rama Dwi Rendra Graha (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research focuses on the employment contract relationship between land-owning farmers and farm workers in Klompangan Village, Ajung District. The goal is to understand how land ownership and management structures affect life and the economy of both. Agriculture in Klompangan Village acts as a provider of employment and a source of income, as well as an important element in the social and economic structure. The research method uses a qualitative approach with case studies, involving field observations and in-depth interviews with farmers who own land and farm workers. The research results show a symbiotic relationship between the two. Farmers who own land need farm laborers to work on land they cannot work on themselves, while farm laborers need access to the land to earn income. This mutual dependence affects the well-being and economy of both, including income, living conditions, and job security. The ultimate goal of this research is to provide insight into how agricultural workers can prosper with fair wage distribution and cooperation between both parties in the rural agricultural sector, which contributes to stability and shared prosperity.